English writing motivational orientation and apprehension among urban and rural Malaysian school students - Shammodin, Najehah (2018)
Geographical background can influence the Malaysians’ English language acquisition. The Malaysian school students’ English writing motivational orientations and apprehension levels based on urban-rural background differences were examined. The correlation between both psychological states was also examined in this study. A total of 264 Malaysian school students (134 urban, 130 rural) participated and responded to the bilingual instruments English Writing Self-Regulation Questionnaire (EWSRQ) and English Writing Apprehension Scale (EWAS). Data were analyzed using SPSS (version 20) through Independent Samples T-test and Pearson Product-Moment Correlation Coefficient analyses. Findings from this study is contrary with results from past literature with regards to urban and rural background differences in Malaysian school students’ English writing motivational orientations and English writing apprehension levels. Urban-rural background caused no significant difference in the scores of Extrinsic, Introjection, and Intrinsic, while there were significant differences in the scores of Identification and Apprehension. These results indicated that the urban-rural categorization of the learning background has influenced the respondents’ motivation to write for own better future (Identification) and in being abnormally anxious when writing in English (Apprehension). The significant relationship between motivational orientations and apprehension suggested that the more reduced autonomy or the more externalized in the students’ orientation of English writing motivation, the more apprehensive they are when writing in the language. Educators and curriculum developers can benefit from this study on the importance of creating student-centered learning climate as a way to reduce students’ detrimental feeling towards English writing. Recommendations for further study are also proposed as a way to improve English language curriculum in Malaysia.